2017
DOI: 10.1038/srep43329
|View full text |Cite
|
Sign up to set email alerts
|

Rainfall reduction amplifies the stimulatory effect of nitrogen addition on N2O emissions from a temperate forest soil

Abstract: Soil is a significant source of atmospheric N2O, and soil N2O emissions at a global scale are greatly affected by environment changes that include continuous deposition of atmospheric nitrogen and changing precipitation distribution. However, to date, field simulations of multiple factors that control the interaction between nitrogen deposition and precipitation on forest soil N2O emissions are scarce. In this study, we conducted a 2-year continuous assessment of N2O emissions from November 2012 to October 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 49 publications
1
11
1
Order By: Relevance
“…Only a few precipitation exclusion experiments have been conducted, but they were not focused on savanna ecosystems (Table S2). In the Yuanjiang savanna, precipitation exclusion had a significant negative effect on N 2 O emissions, which is similar to the effect of precipitation exclusion observed in some other ecosystems (Geng et al, 2017;Wood and Silver, 2012); however, this finding contradicts some studies that showed positive effects (Cattânio et al, 2002;Wieder et al, 2011).…”
Section: Effects Of Precipitation Exclusioncontrasting
confidence: 42%
See 2 more Smart Citations
“…Only a few precipitation exclusion experiments have been conducted, but they were not focused on savanna ecosystems (Table S2). In the Yuanjiang savanna, precipitation exclusion had a significant negative effect on N 2 O emissions, which is similar to the effect of precipitation exclusion observed in some other ecosystems (Geng et al, 2017;Wood and Silver, 2012); however, this finding contradicts some studies that showed positive effects (Cattânio et al, 2002;Wieder et al, 2011).…”
Section: Effects Of Precipitation Exclusioncontrasting
confidence: 42%
“…4). The decrease in the net nitrification and nitrogen mineralization rates inhibited the growth and activity of nitrifying bacteria and decreased the production of N 2 O (Chen et al, 2017;Geng et al, 2017;Hartmann and Niklaus, 2012;Shi et al, 2012). In the meantime, precipitation exclusion decreased the DOC (Table 2).…”
Section: Effects Of Precipitation Exclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, plant N uptake could also cause isotope fractionating processes leading to N losses depleted in 15 N, enriching soil N with the heavier isotope (Evans 2001). The previous study in the experiment site showed that N addition significantly increased N 2 O emission (Geng et al 2017), which could partially explain the increase of soil δ 15 N value. Soil N availability is the source of plant N of non-N 2 -fixing plants; thus the change of plant δ 15 N value (foliage and root) was directly linked to the increase of soil δ 15 N value (Table 4).…”
Section: Effects Of Simulated Nitrogen Deposition On Ecosystem C and N Cyclingmentioning
confidence: 93%
“…Precipitation increases the water‐filled pore space in soils and restricts the availability of O 2 , again favoring complete denitrification (Davidson, 1992; de Klein et al., 1996; Rudaz, Wälti, Kyburz, Lehmann, & Fuhrer, 1999). Geng, Chen, Han, Wang, and Zhang (2017) reported that rainfall reduces the stimulatory effect of the addition of N on N 2 O emissions.…”
Section: Discussionmentioning
confidence: 99%